2010
DOI: 10.1007/s12519-011-0246-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental health in families of children with spina bifida

Abstract: spina bifida, recent stressful life change events and maternal perception of a child as 'difficult' are associated with poor maternal psychological health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…21 In the USA, Vachha and Adams 13 found that caregiver perceptions of having a difficult-to-manage child were significantly correlated with negative mood, more intensity of response and less adaptability. Recent studies from Malaysia and Canada 25,26 found that a large proportion of mothers of children with spina bifida had higher mean total PSI-SF and subscale scores and experienced clinically significant levels of stress compared with those of the controls. Wiegner and Donders 23 found that parents of children with congenital disabilities have adaptive distributions of responsibilities for dealing with domestic tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In the USA, Vachha and Adams 13 found that caregiver perceptions of having a difficult-to-manage child were significantly correlated with negative mood, more intensity of response and less adaptability. Recent studies from Malaysia and Canada 25,26 found that a large proportion of mothers of children with spina bifida had higher mean total PSI-SF and subscale scores and experienced clinically significant levels of stress compared with those of the controls. Wiegner and Donders 23 found that parents of children with congenital disabilities have adaptive distributions of responsibilities for dealing with domestic tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Kazak and Clark 24 found that families of children with myelomeningocele were found to have higher levels of stress than the comparison families. Recent studies from Malaysia and Canada 25,26 found that a large proportion of mothers of children with spina bifida had higher mean total PSI-SF and subscale scores and experienced clinically significant levels of stress compared with those of the controls.…”
Section: Discussionmentioning
confidence: 99%
“…A proper system should be in place for urological management because it is integral in ensuring that spina bi da patients have a better quality of life and improved health continuity 4 . Despite that, Malaysia has yet to set up a proper standard operating procedure for spina bi da individuals from birth as well as their support system towards building a better quality of life 5,6 . Furthermore, kidney health accounts for approximately 70% survivability of these children 7 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Vermaes and colleagues (2008) found that parent personality traits including extraversion (mothers only), emotional stability, and agreeableness (fathers only) related to lower parent stress in parents of children with SB. Additional factors that have been shown to be associated with greater stress and poorer psychological adjustment for parents of children with SB include single parenthood (Kanaheswari, Razak, Chandran, & Ong, 2011; Ong, Norshireen, & Chandran, 2011), avoidant coping style (Barakat & Linney, 1995), lower socioeconomic status (Holmbeck et al, 2002; Malm-Buatsi et al, 2015), older child age (Driscoll et al, 2018; Macias et al, 2007), and higher rates of internalizing (Friedman, Holmbeck, Jandasek, Zukerman, & Abad, 2004; Lemanek, Jones, & Lieberman, 2000) and externalizing (Ridosh, Sawin, Klein-Tasman, & Holmbeck, 2017) symptoms in children.…”
mentioning
confidence: 99%
“…The PSS has demonstrated a moderate to strong relationship with the Parenting Stress Index (PSI; Abidin, 1995), a well-known instrument used to measure stress in a parent–child system. Research studies that have used the PSI to measure parent stress have found parental stress to be elevated in parents of children with neural tube defects compared to parents of children without chronic health conditions (Ong et al, 2011; Vermaes et al, 2008). In addition, the PSS and the PSI have shown similar findings of increased stress in mothers of children with developmental disabilities and behavioral problems compared to mothers of typically developing children (Beckman, 1991; Berry & Jones, 1995).…”
mentioning
confidence: 99%